2020
DOI: 10.1371/journal.pone.0237072
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in persons at risk of developing rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is associated with an increased cardiovascular disease (CVD) risk which may start even before diagnosis. To explore this CVD risk prior to RA, we determined multiple risk factors and two 10-year clinical risk scores in a cohort of individuals at-risk of RA. We also analyzed associations with arthritis development and autoantibody status and compared a subset of at-risk individuals to an age and sex matched seronegative control group. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Given that ACPA-positive RA patients exhibit a higher risk of atherosclerosis compared to those without ACPA [ 17 , 18 ], we examined the association between HDL-related metabolites and the positivity of ACPA. The lipidomic data heatmap illustrates the relative amounts ( Figure 2 A) and the mean levels of discriminant HDL-related metabolites between ACPA-positive and ACPA-negative RA patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ACPA-positive RA patients exhibit a higher risk of atherosclerosis compared to those without ACPA [ 17 , 18 ], we examined the association between HDL-related metabolites and the positivity of ACPA. The lipidomic data heatmap illustrates the relative amounts ( Figure 2 A) and the mean levels of discriminant HDL-related metabolites between ACPA-positive and ACPA-negative RA patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, the changes in HDL size and HDL-related metabolites in RA patients have yet to be fully studied using lipid/metabolomics. Besides, given that anti-citrullinated peptide antibody (ACPA) positive RA patients exhibit a higher risk of ASCVD compared to those without ACPA [ 17 , 18 ], lipid/metabolomics might be a useful tool to find the differential HDL-related metabolites linked to ACPA positivity.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study, 79 patients who later developed RA had higher TC and lower HDL cholesterol levels than those in controls ( 35 ). However, a 10-year cohort study found that lipid changes commenced prior to RA diagnosis ( 36 ). In another retrospective study, RA patients displayed lower mean TC (by 10%) and LDL (by 17%) but no significant difference in HDL levels when compared with those in non-RA controls in the 5 years preceding diagnosis ( 34 ), revealing that dyslipidemia and RA might have a similar pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a major extra-articular manifestation and comorbidity in RA, increasing morbidity and premature CVDrelated mortality [3,4]. Except for the traditional cardiovascular risk factors, like diabetes, hypertension, and hyperlipidemia, the severity of in ammation in RA patients would also increase the risk of CVD [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%